ORIENTATION PROGRAMME FOR FIRST YEAR MEDICAL STUDENTS. A QUALITATIVE STUDY: Orientation Programme - Khan, Khola Waheed; Ramzan, Musarat; Bibi, Saana (Pakistan Armed Forces Medical Journal, 2018)
Objective: To estimate the perceptions of the students regarding its usefulness in academic and future prospectsand to get a clear picture of having promoted learning and ascertaining the standardsStudy Design: A mixed methods research design was adopted.Place and Duration of Study: Wah Medical College Wah Cantt, from Nov 2016 to Oct 2017.Material and Methods: Sixty-five students of the first year MBBS were given questionnaire, quantitative data onthe feedback of orientation week was analyzed through the SPSS version 21. Likert based statistics were analyzedas mean ± SD. The significance of gender related responses was found out by using Chi square test at a p-value of0.05. The qualitative data was analyzed to identify emerging themes.Results: Out of 65 students 26 (40%) were males and 39 (60%) were females. About half of the students (44.6%)strongly agreed that the objective were clearly communicated. About 46.2% of the students felt that theenvironment was safe and conducive for learning. Qualitative analysis generated nine themes in which the mostimportant were the future impact of the orientation week, interactive teaching, the concepts of medical ethics andprofessionalism.Conclusion: The students found that the topics discussed during the orientation week were of great relevance andtime allocated was adequate. However, it unfolded a couple of topics that needed more elaboration which couldbe incorporated in the upcoming years.